2016
DOI: 10.3389/fphar.2016.00360
|View full text |Cite
|
Sign up to set email alerts
|

Garlic and Resveratrol Attenuate Diabetic Complications, Loss of β-Cells, Pancreatic and Hepatic Oxidative Stress in Streptozotocin-Induced Diabetic Rats

Abstract: The study was aimed at finding the effect of garlic and resveratrol on loss of β-cells and diabetic complication in streptozotocin (STZ)-induced Type-I diabetic rats. Rats were injected with single dose STZ (50 mg/kg, i.p.) for induction of type 1 diabetes (Dia) and compared with control group. Rats from third (Dia+Gar), fourth (Dia+Resv), and fifth (Dia+Met) groups were fed raw garlic homogenate (250 mg/kg/day), resveratrol (25 mg/kg/day), and metformin (500 mg/kg/day) orally, respectively, for a period of 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 52 publications
1
49
0
1
Order By: Relevance
“…A previous study suggested that flavonoids exerted the antidiabetic effects via action on various molecular targets, including regulation of glucose metabolism in hepatocytes, increasing glucose uptake by the skeletal muscle and white adipose tissue [4]. Another study revealed that phytochemical compounds, such as garlic acid and resveratrol, decreased pancreatic β-cell damage in STZ-induced diabetic rats and suggested that the antidiabetic mechanism might invlove stimulation of insulin secretion or release of bound insulin [15]. However, VC supplementation in diabetic rats did not alleviate the body weight and food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that flavonoids exerted the antidiabetic effects via action on various molecular targets, including regulation of glucose metabolism in hepatocytes, increasing glucose uptake by the skeletal muscle and white adipose tissue [4]. Another study revealed that phytochemical compounds, such as garlic acid and resveratrol, decreased pancreatic β-cell damage in STZ-induced diabetic rats and suggested that the antidiabetic mechanism might invlove stimulation of insulin secretion or release of bound insulin [15]. However, VC supplementation in diabetic rats did not alleviate the body weight and food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the fenugreek seeds [34], Marrubium vulgare [35], N. sativa [36], A. sativum [37], Carum carvi, and Ziziphus lotus [38,39] shows an antidiabetic effects in streptozotocininduced diabetic in rat and alloxan-induced diabetes in mice. Khan et al demonstrated in vitro that P. dactylifera seeds extract inhibit α-glucosidase and α-amylase level [40].…”
Section: Discussionmentioning
confidence: 99%
“…Arteriosclerosis, management of diabetes mellitus, asthma, deafness, leprosy, bronchial congestion, fevers, worms, and liver gall bladder trouble [180] Antidiabetic, hepatoprotective, antimicrobial, and antihyperlipidemic activities [181] Annona muricata L.…”
Section: Growth Habit Parts Used Preparation and Mode Ofmentioning
confidence: 99%